Uncovering the Role of Gut Microbiota in Amino Acid Metabolic Disturbances in Heart Failure Through Metagenomic Analysis - Hayashi, Tomohiro; Yamashita, Tomoya; Takahashi, Tomoya; Tabata, Tokiko; Watanabe, Hikaru; Gotoh, Yasuhiro; Shinohara, Masakazu; Kami, Kenjiro; Tanaka, Hidekazu; Matsumoto, Kensuke; Hayashi, Tetsuya; Yamada, Takuji; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims: Circulating amino acid (AA) abnormalities serve as predictors of adverse outcomes in patients with heart failure (HF). However, the role of the gut microbiota in AA disturbances remains unknown. Thus, we investigated gut microbial functions and their associations with AA metabolic alterations in patients with HF. Methods and result: We performed whole-genome shotgun sequencing of fecal samples and mass spectrometry-based profiling of AAs in patients with compensated HF. Plasma levels of total essential AAs (EAAs) and histidine were significantly lower in patients with HF than in control subjects. HF patients also displayed increased and decreased abundance of gut microbial genes involved in the degradation and biosynthesis, respectively, of EAAs, including branched-chain AAs (BCAAs) and histidine. Importantly, a significant positive correlation was observed between the abundance of microbial genes involved in BCAA biosynthesis and plasma BCAA levels in patients with HF, but not in controls. Moreover, network analysis revealed that the depletion of Eubacterium and Prevotella, which harbor genes for BCAA and histidine biosynthesis, contributed to decreased abundance of microbial genes involved in the biosynthesis of those EAAs in patients with HF. Conclusions: The present study demonstrated the relationship between gut microbiota and AA metabolic disturbances in patients with HF.